Assessing the social benefits to stakeholders of place-based forest restoration organizations in Colorado - Lund Snee, Torsten A., author; Seidl, Andrew, advisor; Loomis, John, committee member; Cheng, Antony, committee member (Colorado State University. Libraries, 2015)
Collaborative forestry organizations such as the Front Range Roundtable provide goods and services to their members which have not yet been valued using economic methodology. The primary good provided by the Front Range Roundtable is quarterly stakeholder meetings where proposed landscape restoration projects are discussed and members are able to reach consensus on appropriate monitoring and implementation without resorting to legal measures. Attendance at these meetings suggests that members derive benefits from attendance and have a positive willingness-to-pay for these goods. This study contributes to the natural resource and environmental economics literature by estimating values associated with the social capital that is developed at collaborative forestry meetings, and should serve to inform the policy debate regarding funding of place-based forestry collaboratives. Attendees at the April 11, 2014 quarterly meeting of the Front Range Roundtable were asked travel cost questions and a dichotomous choice willingness to pay question regarding membership dues for the Front Range Roundtable's quarterly meetings. Results from 50 paper and online surveys indicate that respondents would pay a minimum of $6.60 per quarter to travel to the FRR's quarterly meetings, and a maximum of $83 in membership dues to allow the FRR to continue to provide conflict mediation and resolution services. Generalizing these amounts to the sample yields an annual value of $1,241 for minimum WTP for travel expenses and an annual value of $16,609 for FRR's mediation and conflict resolution services.
Keywords: contingent valuation; social benefits; travel cost model; economics; community forestry; social capital